Syndrome in question - Priscila Regina Orso Rebellato; Camila Makino Rezende; Eveline Roesler Battaglin; Brunno Zeni de Lima; Jose Fillus Neto (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Morbihan Syndrome is a rare entity with unknown etiology. It is clinically characterized by chronic erythematous edema on the face - especially in the middle and upper third of the face - and creates abnormal facial contours that are initially intermitent but become permanent with the development of the syndrome. The histopathology is nonspecific and its therapy is a major challenge due to poor response to the various treatment options. We present the case of a male patient with a five-month-history of disease.